2018
DOI: 10.1038/s41467-018-03163-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging risks from marine heat waves

Abstract: Recent marine heat waves have caused devastating impacts on marine ecosystems. Substantial progress in understanding past and future changes in marine heat waves and their risks for marine ecosystems is needed to predict how marine systems, and the goods and services they provide, will evolve in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
348
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(355 citation statements)
references
References 24 publications
4
348
0
3
Order By: Relevance
“…Marine heatwaves are known to severely affect ecosystem structure via mass bleaching, low primary productivity, and wide mortality of sea animals. In comparison with terrestrial climate extreme impacts, we found fewer reports of the impact of marine climate extremes on organisms and ecosystems (Frolicher & Laufkotter, ).…”
Section: Discussionmentioning
confidence: 62%
“…Marine heatwaves are known to severely affect ecosystem structure via mass bleaching, low primary productivity, and wide mortality of sea animals. In comparison with terrestrial climate extreme impacts, we found fewer reports of the impact of marine climate extremes on organisms and ecosystems (Frolicher & Laufkotter, ).…”
Section: Discussionmentioning
confidence: 62%
“…Other sources of bias are atmospheric aerosols, and instrument design and aging. Despite these biases, NOAA‐OI has been widely used in MHW studies due to its temporal and spatial resolution, long record, and global coverage (e.g., Frölicher & Laufkötter, ; Hobday et al, ; Holbrook et al, ; Manta et al, ; Oliver et al, ; Smale et al, ). The results relative to NOAA‐OI presented here are comparable to previous MHW studies—because the same biases are present in those studies.…”
Section: Methodsmentioning
confidence: 99%
“…This NE Pacific MHW (“the Blob”) is defined as a severe MHW since SST anomalies reached 3 times the 90th percentile differences from the local climatological SSTs (Hobday et al, ). MHWs are increasing in severity and frequency, and this trend will likely continue into the future due to climate change (Oliver, Donat, et al, ); consequently, it is prudent to understand the physical drivers that start and maintain MHWs (Frölicher & Laufkötter, ; Oliver, Benthuysen, et al, ). The onset of the high SSTs in the NE Pacific was associated with a ridge of high pressure that persisted over the Gulf of Alaska region for many weeks, stagnating winds and causing anomalous atmosphere–ocean heat fluxes (Bond et al, ; Gentemann et al, ; Hartmann, ).…”
Section: Introductionmentioning
confidence: 99%